ENERGY EFFICIENT WATER DESALINATION TECHNOLOGY - Ezhov, Vladimir Sergeevich; Semicheva , Natalia Evgenievna; Ezhova , Tatiana Vladimirovna; Brezhnev , Artem Viktorovich (Journal of Applied Engineering Science, 2020)
The work relates to the technique of desalination of sea and saline waters and can be used to obtain desalinated water with generation of electrical energy. The proposed technology of water desalination is implemented by an autonomous solar desalination-electric generator, containing a rectangular body, the roof of which is covered from above with photocells with a storage unit, an inclined evaporating tray is placed inside the body, dividing the body cavity into evaporation and condensation chambers, communicating with each other at the sides of the body through vertical slots at the ends of the body and the tray are an inlet manifold connected to a submersible feed pump, and a horizontal outlet slot. The bottom of the body is connected to a condensate collection tank, in which a condensate pump is placed, a condensation chamber, immersed in a reservoir, the inner surface of the ends, sides and bottom of the condensation the chamber is made with vertical and horizontal corrugations, into the grooves of which thermoelectric converters are inserted. The first and last of which with photocells are connected to the output collectors, a storage unit, feed and condensate pumps and other them as consumers of electricity.